PENGARUH LIKUIDITAS, SOLVABILITAS DAN TATO TERHADAP HARGA SAHAM PADA PERUSAHAAN SEKTOR PROPERTY &REAL ESTATE DI BEI - Febby Yolanda Sijabat; Rohani Hutahaean; Diana Hutahaean; Rison Pardede (Lembaga Penelitian dan Pengabdian Kepada Masyarakat-Universitas Darma Agung. (LPPM_UDA), 2021)
Currently the property and real estate sector is a sector that developers consider increasingly attractive and prospective in 2018. The purchasing power of the society will increase in 2018 and will be higher than 2017. This research aimed at testing and analyzing the effect of the current ratio, debt to equity ratio and total asset turn over on the stock price of the property and real estate sector companies listed in Indonesia Stock Exchange in the 2014-2018 period. The method used was multiple linear regression. The hypothesis testing using the test model (test F) indicated that the current ratio, debt to equity ratio, the total asset turn over had significant effect on the stock price. The result of a hypothesis test conducted using a partial test (Test T) indicated that the current ratio had no effect and was not as important as the stock price. Total turn over assets were influential and insignificant. While debt to equity ratios were influential and significant to the stock price. The result of the analysis of coefficient of determination obtained the adjusted value of R Square (R2) of 0.115 or 11.5%. This meant that 11.5% of stock price could be explained by the variation of the independent variables, namely Current Ratio, Debt to Equity Ratio and Total Asset Turn Over. While the remaining 88.5% was described by other variables